Storage stability and solubilization ability of HPMC in curcumin amorphous solid dispersions formulated by Eudragit E100. (1st November 2018) - Fan, Na; Ma, Pingping; Wang, Xin; Li, Chang; Zhang, Xiaorui; Zhang, Kexin; Li, Jing; He, Zhonggui
Highlights: HPMC had the ability to inhibit crystallization and maintain stability in Cur ASDs. As a non-ionic surfactant, HPMC was able to increase solubilization of Cur. Cur-E100/HPMC 6:1 was superior in improving dissolution and maintaining stability. Abstract: The present study elucidated the advantages of using hydroxypropyl methylcellulose E5 (HPMC) as auxiliary excipient in maintaining storage stability and solubilization ability for curcumin amorphous solid dispersion (Cur ASDs) formulated by Eudragit E100 (E100). Polarized light microscopy and in vitro dissolution experiment was applied for confirming the ability of HPMC on inhibiting crystallization thereby maintaining storage stability in Cur ASDs. Meanwhile, as a non-ionic surfactant, HPMC can form micelles in pH 1.0 hydrochloric acid and played a role in solubilization ability on Cur. Critical micelle concentration (CMC), molar solubilization ratio (MSR) and micelle-water partition coefficient Kmc of surfactants (HPMC, E100/HPMC 1:1 and E100/HPMC 6:1) in pH 1.0 hydrochloric acid were calculated to determine the solubilization ability of surfactants. The results showed that the solubilization ability of E100/HPMC 6:1 was the best and the solubilization mechanism of E100/HPMC 6:1 was also different from HPMC and E100/HPMC 1:1.